ACE gene variants and sarcoidosis in a Finnish population - Lahtela, Elisa; Wennerstrom, Annika; Pietinalho, Anne; Petrek, Martin; Kolek, Vitezslav; Lokki, Marja-Liisa; Selroos, Olof (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2017)
Background: Sarcoidosis is a systemic inflammatory disease with unknown etiology. However, there is a strong evidence of genetic influence in sarcoidosis. Objectives: We wanted to extend our knowledge of the role of the whole ACE gene, not only insertion/deletion (I/D) polymorphism, in a Finnish sarcoidosis population by genotyping the ACE gene region from 5’ upstream to the 3’ downstream. Methods: We genotyped 29 single nucleotide polymorphisms (SNPs) spanning the ACE gene from 188 sarcoidosis patients (resolved disease, n=90; persistent disease, n=98) and from 150 controls. These SNPs included tag SNP rs4343 for I/D polymorphism. To replicate the study we genotyped 11 of these SNPs from 139 Czech sarcoidosis patients (resolved disease, n=47; persistent disease, n=92) and 176 healthy controls. Results: No association was detected between I/D genotypes and disease susceptibility or prognosis. We found a novel SNP (rs9905945) in the 5’upstream region of the ACE gene to be moderately associated with favourable disease prognosis in Finnish patients [p=0.035, OR=2.034 (95%CI 1.045-3.960)]. However, in the replication study in Czechs, the SNP rs9905945 did not show association with prognosis of sarcoidosis. Conclusions: This study further characterizes genetic distinctions between Finnish sarcoidosis patients with different prognosis and population-specific genotype distribution of ACE variants. Nevertheless it seems that variants in the ACE gene do not considerably influence the course of the disease in Finnish sarcoidosis patients.